Influence of Topographic Effect on Dynamic Behavior of Hill Slope Building - N. Gajurel; S. Manandhar; M.R. Bhatt (Lowland Technology International, 2020)
This research was driven by observations made during the April 2015 Gorkha Earthquake, in which buildings located on the cliffs and hillslopes suffered significant damage. The primary goal of this research is to study the impact of topography on the dynamic behavior of buildings located on the slopes of hills, which are popular residential sites spread across Nepal. The numerical simulation of topographic effect was done using Ground Response Analysis. 2D geological models were made, over which seismic simulation were done. The results are presented in the form of topographical amplification factor (TAF). The amplification factor calculated from ground response analysis were used in static and linear dynamic time history analysis of the buildings. The response of a two-storied structure is compared with and without considering the effect of topography. The outcome demonstrates that, owing to topographic impact, hill-slope structures built using contemporary seismic design codes are not sufficient to withstand the enhanced seismic forces.